Pengaruh Pembelajaran Berdiferensiasi Berbantuan Booklet terhadap Kemampuan Literasi Dasar dan Motivasi Belajar Siswa Kelas II SD Unggulan Hamzanwadi Tahun Ajaran 2024/2025 - Algae, Risqi Arilia; Haritani, Hartini; Ali, Muhammad (Universitas Hamzanwadi, 2024)
The objective of this research is to examine the simultaneous impact of differentiated instruction supported by booklets on foundational literacy and student motivation at SDU Hamzanwadi Selong. Foundational literacy and differentiated instruction are integral to the Merdeka Curriculum, launched in 2021 by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) through various initiatives, including the